L' arrestation de Jésus en Marc 14,43-52: etude structurelle - Auffret, Pierre (Biblische Notizen, 2014)
According to R. Meynet the author attempts to adjust further structural analysis of the story of the arrest of Jesus in Mark. Proceeding from smaller units he finds further structured sub-units which exist of Mc 14, 43-47 and 44b-52, from which results the overall structure.